THE STUDY ON THE EFFECT OF PROCESS VARIABLES TOWARDS BIOADSORBENT PERFORMANCE OF MODIFIED PALM BUNCH FOR THE REDUCTION OF 3-MCPD ON THE PALM OIL - Wahyuningsih Wahyuningsih; Mohamad Endy Yulianto; Rizka Amalia; Eflita Yohana (Waste Technology, 2017)
Crude palm oil was consumed as a healthy food oil, it contains a 3-monochloro-propane-1,2-diol (3-MCPD) ester in the range of 0.04-0.05 ppm. The 3-MCPD compound is one of the contaminants belonging to the chloropropanol group that is genotoxin carcinogen. The 3-MCPD ester content specification in palm oil is still a polemic, but some EU countries already use it as a barrier of palm oil trade in the European region. It is therefore necessary to develop an integrated palm oil refining through adsorption with a modified palm empty fruit bunch bioadsorbent to reduce 3-MCPD ester (<0.02 ppm / Codex Standard).